The hegemony of psychopathy - Brons, Lajos (Brainstorm Books, 2017)
Any social and political arrangement depends on acceptance. If a substantial part of a people does not accept the authority of its rulers, then those can only remain in power by means of force, and even that use of force needs to be accepted to be effective. Gramsci called this acceptance of the socio-political status quo "hegemony." Every stable state relies primarily on hegemony as a source of control. Hegemony works through the dissemination of values and beliefs that create acceptance and that serve the interests of the state and/or the ruling elite (the "hegemones"). Hegemony is most efficient if it remains invisible. A key hegemonic belief is the idea that there is no alternative to the current socio-political status quo or that the way things are is "natural." The current hegemony - that is, the set of values and beliefs that bolster the current socio-political status quo - is a hegemony of psychopathy: it promotes "cultural psychopathy" and destroys empathy and compassion, thus threatening everything that makes us human. The hegemony of psychopathy is responsible for massive human suffering. It must be fought and replaced with a counter-hegemonic set of values and beliefs that promote compassion and care. Fighting hegemony requires fighting the "pillars" that support it. Most important among these are the mass media and culture industry, and mainstream economics. The former is responsible for a continuous stream of hegemonic propaganda; the latter - among others - for providing a pseudo-scientific justification for the false belief that there is no alternative. The Hegemony of Psychopathy concludes with some considerations on tactics and strategy in the struggle against the hegemony of psychopathy, but does not - and cannot - offer any concrete advice